Challenges and concepts in the diagnosis and management of ocular graft-versus-host disease - Tappeiner, Christoph; Heiligenhaus, Arnd; Halter, Joerg P.; Miserocchi, Elisabetta; Bandello, Francesco; Goldblum, David (Frontiers in Medicine, 2023)
Graft-versus-host disease (GVHD) is characterized by tissue inflammation in the host following an allogeneic hematopoietic cell transplantation (HCT). The pathophysiology is complex and only incompletely understood yet. Donor lymphocyte interaction with the histocompatibility antigens of the host plays a crucial role in the pathogenesis of the disease. Inflammation may affect multiple organs and tissues, e.g., the gastrointestinal tract, liver, lung, fasciae, vaginal mucosa, and the eye. Subsequently, alloreactive donor-derived T and B lymphocytes may lead to severe inflammation of the ocular surface (i.e., cornea and conjunctiva) and the eyelids. Furthermore, fibrosis of the lacrimal gland may lead to severe dry eye. This review focuses on ocular GVHD (oGVHD) and provides an overview of current challenges and concepts in the diagnosis and management of oGVHD. Ophthalmic manifestations, diagnostic procedures, grading of severity and recommendations for ophthalmic examination intervals are provided. Management of ocular surface disease with lubricants, autologous serum eye drops, topical anti-inflammatory agents and systemic treatment options are described based on the current evidence. Ocular surface scarring and corneal perforation are severe complications of oGVHD. Therefore, ophthalmic screening and interdisciplinary treatment approaches are highly relevant to improve the quality of life of patients and to prevent potentially irreversible visual loss.